Strategi transendensi tokoh perempuan melawan budaya patriarki dalam novel Mendhung Angendanu karya Budiono Santoso Setradjaja - Trestanti, Febriani Anggi; Fuadhiyah, Ucik (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to apply Simone de Beauvoir’s existentialist feminism in revealing the forms of gender injustice and transcendence strategies on female characters in the Mendhung Angendanu novel by Budiono Santoso Setradjaja. The descriptive qualitative method, which uses data collection techniques through reading and recording, is an important part of this research. The data analyzed are words, sentences, or paragraphs that show gender injustice and transcendence strategies applied by female characters. Data sources consist of primary and secondary data. The primary data source is the novel Mendhung Angendanu by Budiono Santoso Setradjaja, which consists of 303 pages and was published in 2022 in Sleman, Yogyakarta. Secondary data sources come from articles and books relevant to the research problem. The findings show that in the novel, female characters experience gender injustice in the form of subordination, marginalization, violence, and workload. In addition, it was found that the transcendence strategies carried out by female characters include working women, intellectual women, women who contribute to social transformation, and women who refuse to internalize the values of injustice.